Patient journey method for integrated service design. Issue 1 (2nd January 2019) - Simonse, Lianne; Albayrak, Armaĝan; Starre, Susan
Abstract: In this article, we focus on the design method of mapping the patient journey in order to support the inclusion of the patient perspective into care service innovations. Increasingly, designers in health use the patient journey approach, however, its method is relatively poorly documented. To ground the activities of the patient journey method, we conducted an in-depth case study of integrated service design with impact on improved patient satisfaction – the case of gastrointestinal diagnose service with video endoscopy technology. The results revealed four distinct activities of the patient journey method: (1) Analyse the care service system; (2) Experience the journey yourself, observe and sketch it; (3) Co-design the patient journey: craft the journey toolkit, interview and synthesize; (4) Evaluate the patient journey for integrated service design.